2009
DOI: 10.1038/cmi.2009.26
|View full text |Cite
|
Sign up to set email alerts
|

H. pylori Escape Host Immunoreaction Through Inhibiting ILK Expression by VacA

Abstract: Helicobacter pylori (H. pylori) persistently colonizes the gastric mucosa despite a vigorous immune response. Vacuolating cytotoxin secreted by H. pylori has turned out to be a potent immunomodulatory toxin, but the signal transduction pathways involved has not been studied in macrophages. We observed in this study that vacA-deficient H. pylori induced significantly higher expression of integrin-linked kinase (ILK) and endothelial nitric oxygen synthase (eNOS), and significantly more production of reactive oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Bacterial arginase and γ-glutamyl transferase show similar functions in altering the normal function of T-cells [74,75], while arginase and VacA additionally downregulate the expression of inducible nitric oxide synthase [76,77].…”
Section: Manipulation Of the Immune Systemmentioning
confidence: 99%
“…Bacterial arginase and γ-glutamyl transferase show similar functions in altering the normal function of T-cells [74,75], while arginase and VacA additionally downregulate the expression of inducible nitric oxide synthase [76,77].…”
Section: Manipulation Of the Immune Systemmentioning
confidence: 99%
“…Megasomes show a limited lumenal acidification and acquire only a limited amount of late endosomal/lysosomal markers [221]. Moreover, Yuan et al [223] suggested that VacA may favor H. pylori survival in macrophages by decreasing ROS production in such cells through inhibition of the expression of endothelial nitric oxygen synthase mediated by a suppressive effect of the toxin on the expression of integrin-linked kinase. However, a VacA role in H. pylori-induced homotypic phagosome fusion or prolonged intracellular survival of bacteria in human monocytes has been challenged by Rittig et al [224].…”
Section: Effects On Phagocytosis and Antigen Presentationmentioning
confidence: 97%
“…It usually causes chronic infection and persists for the life of the host and is not eradicated despite a vigorous immune response was raised by host immune system [3], suggesting that the bacterial reserve some mechanisms for escaping from host immune response, such mechanisms have been under extensive study and reported elsewhere [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%